Association of Paraspinal Muscle CSA and PDFF Measurements With Lumbar Intervertebral Disk Degeneration in Patients With Chronic Low Back Pain - Huang, Yilong; Wang, Ling; Zeng, Xiaomin; Chen, Jiaxin; Zhang, Zhenguang; Jiang, Yuanming; Nie, Lisha; Cheng, Xiaoguang; He, Bo (Frontiers in Endocrinology, 2022)
There is an interaction between the lumbar spine and paraspinal muscles, which may play a role in the development of intervertebral disc (IVD) degeneration and may affect CLBP. The study aims to assess the relationship between IVD degeneration and paraspinal muscle fat infiltration in CLBP patients by quantitative MR imaging, and to evaluate the influence of sex and age on CLBP muscle fat infiltration. Sixty CLBP patients (46.3 years ±17.0) and thirty-two healthy volunteers (44.9 years ±17.6) were recruited for this study. 3.0 T MRI was used to perform the sagittal and axial T1WI, T2WI of the lumbar spine, and axial paraspinal muscle IDEAL imaging at the L4/5 and L5/S1 levels. Proton density fat fraction (PDFF) of the multifidus and erector spinae at two IVD levels were measured. The Pfirrmann grades of IVD degeneration, Oswestry Disability Index (ODI), and Visual Analog Scale (VAS) were also evaluated. Compare the cross-sectional area (CSA) and PDFF of the paraspinal muscles between CLBP patients and healthy volunteers, and analyze the relationship between the muscle PDFF and Pfirrmann grades, sex, and age of CLBP patients. Compared with healthy volunteers, the CSA of the multifidus muscle in CLBP patients decreased (1320.2±188.1mm2 vs. 1228.7±191.0 mm2, p<0.05) at the L4/5 level, the average PDFF, (7.7±2.6% vs. 14.79±5.3%, 8.8±4.2% vs. 16.03±5.3%, all p<0.05) at both L4/5 and L5/S1 levels. The PDFF of paraspinal muscles were correlated with adjacent IVD degeneration, ODI and VSA in CLBP patients (all p<0.05). After using age and body mass index (BMI) as control variables, significance was retained (all p<0.05). Multiple regression analysis revealed sex and age also were significantly associated with multifidus PDFF (all p < 0.05). This study confirmed that the CSA decreased and the PDFF increased of the paraspinal muscles in CLBP patients. It reveals a significant correlation between the PDFF of CLBP paraspinal muscles and the grade of IVD degeneration. Sex and age are also important factors influencing CLBP paraspinal muscle infiltration.